Interferences Between Tradition and Modernity in the Symphonic and Concerto Works by Adrian Pop – (2) Etos I - ȘANDOR, Paula (Studia Universitatis Babes-Bolyai Musica, 2023)
The present study is part of a series of analytical approaches undertaken on the symphonic-concertant oeuvre of Cluj composer Adrian Pop. Following the chronological order of the works and keeping as a reference their common source of inspiration – namely the Romanian folklore –, the conclusion seeks to highlight the way in which the composer’s individuality relates to both the trends of contemporary language and the European cultured musical tradition, without attenuating the signs of the local stylistic matrix. Starting from the melody of a Miorița from Sălaj, whose typology will prove crucial in rendering the Blagian concept of the undulating plain, the composer uses traditional means – in particular the timbral essences and effects specific to folk organology – or contemporary techniques such as spectralism, texturalism, heterophony, to capture both the descriptive aspects of the idyllic universe and the archaic, archetypal, timeless and, last but not least, tragic essences of the philosophical and literary source. The symphonic discourse established at the level of the three main sections of the work follows a path of almost organic development, from the cellular-motivic elements that anticipate the Miorița theme, engaged in homogeneous, pulsating, diaphanous, or extremely dissonant textures, to the unique moment of virtuosity of the two semantroms in the central section and, finally, to the display of the original melody in juxtaposition, or superimposition with its inversion, in a tableau dominated by the ascent and descent of the flocks of sheep.